Time-periodic dynamics in COVID-19 transmission considering the impact of population disbelief and fear - Mahmoud A. Ibrahim; Attila Dénes (Scientific African)
The ongoing COVID-19 pandemic has spurred an urgent need for advanced modeling approaches to understand the complex dynamics of disease transmission. Our model utilizes a system of differential equations that incorporates the impact of both contagious fear and contagious disbelief surrounding the disease on its transmission dynamics. This study presents a time-periodic compartmental model, integrating insights from recent research on time-varying transmission rates. We define the basic reproduction number (R0), emphasizing its utility as a threshold parameter for global dynamics and periodic solutions. Numerical simulations validate the theoretical findings and provide a nuanced understanding of disease persistence and extinction. The impact of population disbelief and fear on the risk of COVID-19 is investigated, revealing critical insights for public health interventions. The sensitivity analysis of the basic reproduction number underscores the significance of key parameters in shaping disease dynamics. Our results provide insight into the intricate dynamics of COVID-19 transmission, offering valuable considerations to control the spread of the virus.